Effectiveness of Truth or Dare Game Media to Train Students' Argumentation Skills on Buffer Solution Material - Tamami, Hilda; Rusmini, Rusmini (Universitas Syiah Kuala, 2024)
In buffer solution material, many students still do not complete it. This is due to the lack of variation in learning media. One of the right media is the truth or dare game. This media can help students to ask, answer questions, and share their ideas, so that it can help train students' argumentation skills which are still relatively low. This study aims to describe the effectiveness of the truth or dare game media to train students' argumentation skills on the buffer solution material. The research design used a pre-experimental design, namely One Group Pretest-Posttest Design. Implementation was carried out on 32 grade XI high school students. The instruments used were argumentation skills test sheets and knowledge learning results test. The data collection method used the test method. Data were analyzed using paired t-tests, N-Gain, along individual and classical completeness tests. The results of the study indicate that the truth or dare game media is effective in training argumentation skills and students complete individually and classically.